Fabrication of p-type ZnO thin films with high mobility using reactive gases N2 and Ar by RF sputtering - A. Ismail; Badr Ismael Abdul-Razak; Motahher A. Qaeed; Ammar AL-Farga (PLoS ONE, 2025)
Co-doping with AlN via RF sputtering is necessary since it is still very difficult to create high conductivity p-type zinc oxide (ZnO) thin films. At room temperature, RF sputtering was used with Ar (20%) and N2 (80%) at a range of target powers (150, 175, 200, 225, and 250 W). All of the produced films displayed the ZnO (002) peak of the wurzite structure. Using the PL approach, the recombination of free excitons was detected. The ZnO:AlN and ZnO:N Raman peaks were observed at 578.58 cm -1 and 276 cm -1 , respectively.With hole concentrations of 3.06 × 10 +16 cm -3 and 1.83 × 10 +18 cm -3 , respectively, and corresponding mobilities of 117 cm 2 V -1 s -1 and 19.1 cm 2 V -1 s -1 , the AZO23 and AZO25 samples demonstrated p-type conductivity behavior. The N-Al-N complex, which forms as a shallow acceptor when Zn +2 ions are substituted by Al +3 ions, is the cause of the p-type behavior of the ZnO sample (AZO23).However, the production of (N) O acceptors due to the substitution of the bigger N -3 ions (radius of 0.146 nm) for the O -2 ions (radius of 0.140 nm), may be the cause of the p-type behavior of AZO25 sample. AZO23 sample has a greater mobility (117 cm 2 V -1 s -1 ) which can be explained by the higher mean free path/crystallite size (̖Ɩ/D) ratio.